Carbon Rule of Law that Determine to be the One in Genome Based Remedy: Viral One under Study - Rajasekaran Ekambaram; Indupriya Rajasekaran (Current Practice in Medical Science Vol. 10, 2022)
Viral proteins’ structural variations can result from mutations. These structural alterations are brought on by carbon distribution. Here, the carbon distribution in viral proteins is examined. Results show that nuclear proteins have lower carbon contents than polymerase proteins and that surface proteins have higher carbon contents. The carbon distribution pattern of polymerase proteins is superior than that of other proteins. As thymine distribution in various mRNA frames is linked to the carbon distribution pattern in the associated proteins, it is examined. Findings indicate that frame 4 violates the distribution of thymine. The synthesis of proteins with various carbon distributions is caused by this. In frame 3, an unusual distribution of thymine is seen. When compared to normal mRNA, the viral mRNA has a distinct thymine distribution. The analysis of mRNA sequence of virus reveals that the adenine content is higher in all sequences. The performance of the protein might be enhanced by reducing the excess thymine in viral mRNAs. It is important to make greater use of mutational research based on carbon distribution to enhance protein stability, activity, and ultimately gene therapy.